Jak Gaja Grzegorzewska skampowała powieść kryminalną - Magdalena Tosik (Literatura i Kultura Popularna)
In 2006 Gaja Grzegorzewska published the first novel (out of six, as per 2024) on the adventures of Julia Dobrowolska, a private eye. Polish critics have acknowledged the series for hybridizing the crime genre with romance and exploring the subject of gender and sexual identity within this generic framework. In my reading of the Dobrowolska series I argue that the way in which the female detective adapts to the gender stereotypes of this profession (traditionally considered as male-dominant) results in introducing camp aesthetics into the series by the means of play with the ‘male gaze’ that is intrinsic to the hard-boiled genre. The paper intends to investigate how Grzegorzewska dismantles the tradition of hard-boiled fiction and re-writes it accordingly to make her female character plausible in this particular literary context through the means of camp aesthetics.